Reidentification of a 19th century specimen reveals the first record of Amphisbaena hogei Vanzolini, 1950 (Squamata, Amphisbaenidae) in Minas Gerais, Brazil - Henrique C. Costa (Evolutionary Systematics)
For almost 60 years, a specimen of Amphisbaena collected in the 19th century by the Danish zoologist Johannes Theodor Reinhardt in southeastern Brazil has been identified as Amphisbaena prunicolor. Here I present a reidentification of this specimen (NHMD R4448) as A. hogei, together with a review of known records of this small worm lizard species, endemic to Brazilian Atlantic Forest. This represents the first record of A. hogei for the state of Minas Gerais. Most known records of A. hogei are based on specimens collected more than half a century ago and urbanization could have led to local extinction in some localities, triggering an alert regarding its conservation status.